Development and testing of the Youth Alcohol Norms Survey (YANS) instrument to measure youth alcohol norms and psychosocial influences. Issue 5 (14th May 2018) - Burns, Sharyn K; Maycock, Bruce; Hildebrand, Janina; Zhao, Yun; Allsop, Steve; Lobo, Roanna; Howat, Peter
Abstract : Objectives: This study aimed to develop and validate an online instrument to: (1) identify common alcohol-related social influences, norms and beliefs among adolescents; (2) clarify the process and pathways through which proalcohol norms are transmitted to adolescents; (3) describe the characteristics of social connections that contribute to the transmission of alcohol norms; and (4) identify the influence of alcohol marketing on adolescent norm development. Setting: The online Youth Alcohol Norms Survey (YANS) was administered in secondary schools in Western Australia Participants: Using a 2-week test–retest format, the YANS was administered to secondary school students (n=481, age=13–17 years, female 309, 64.2%). Primary and secondary outcome measures: The development of the YANS was guided by social cognitive theory and comprised a systematic multistage process including evaluation of content and face validity. A 2-week test–retest format was employed. Exploratory factor analysis was conducted to determine the underlying factor structure of the instrument. Test–retest reliability was examined using intraclass correlation coefficient (ICC) and Cohen's kappa. Results: A five-factor structure with meaningful components and robust factorial loads was identified, and the five factors were labelled as 'individual attitudes and beliefs', 'peer and community identity', 'sibling influences', 'school and community connectedness' and 'injunctive norms', respectively. The instrument demonstrated stability across the test–retest procedure (ICC=0.68–0.88, Cohen's kappa coefficient=0.69) for most variables. Conclusions: The results support the reliability and factorial validity of this instrument. The YANS presents a promising tool, which enables comprehensive assessment of reciprocal individual, behavioural and environmental factors that influence alcohol-related norms among adolescents.